Effect of Fish Transportation on immunological response and Bacterial Diseases in Anabas Testudineus Fish - Hardi, Esti Handayani; Asmir, Asmir; Pebrianto, Catur Agus; Saptiani, Gina; Agustina, Agustina (Aquacultura Indonesiana, 2015)
This study was conducted to determine the condition of immunological response of and the presence of bacterial diseases in Anabas Testudineus fish was transported from pond culture towards Segiri Market. Transport system carried out by the fishmonger supposed to influence the health conditions of fish as well as the presence of bacteria on the fish's body. The sample was 30 fish from Muara Kaman pond and Markets Segiri as a fish marketing. Some parameters were observed among others: changes in swimming behavior, pathology anatomy organs, aemotology and inventory of bacterial diseases. The results showed that the samples of fish from the pond aquaculture generally have normal conditions of organ anatomy, symptom behavior swim also normally, otherwise fish from marketed in the Market Segiri, as much as 60% of fish have abnormal behavior of swimming, 73% have pathology on external anatomy and 53% fish have abnormalities in organs. Results of the isolation and identification of bacterial disease found that there are 5 types of bacteria Aeromonas, Pseudomonas, Staphyllococcus, Streptococcus and Basillus, and only bacteria Staphyllococcus and Basillus not found in fish pond aquaculture origin. The health condition of the fish pond aquaculture origin betook better, judging from the hemoglobin, hematocrit, total leukocyte and total erythrocyte that is within the normal range. While the blood picture fish from Segiri market is generally higher in all parameters that indicate health problems. It can be concluded that the transport system carried out by the wet etching fishmonger effect on the occurrence of abnormalities in behavioral symptoms, anatomic pathology outer and inner organs, the presence of bacterial disease and the decline in fish health conditions.Keywords : Betok fish, bacterial, transportation